Facilities performance audit on public buildings - Md Ariffin, Khadijah; Kasim, Rozilah; Ishak, Mohd Hafizal; Harun, Mohd Rosli; Mohd Noh, Zainuddin (JARDCS, 2018)
Facilities management is an important element in a business organization. These facilities have direct and indirect impact to the main business operation. However, business owners are faced with problems after more than 3 years of operation. This unexpected facility failure disturbs business operation thus facilities performance audit is seen as one of the solution. In order to conduct the facilities performance audit, the list of facilities needed to be identified. This paper seeks to identify the facilities provided at the Faculty of Technology Management and Business, Universiti Tun Hussein Onn Malaysia, which is the case study chosen. A focus group discussion was held with the facilities management department and the buildings user/first-line manager. The focus group has identified the various facilities throughout the building which is listed for audit purposes. The findings are important in order to conduct performance audit on the building and determine the facilities performance of the building